Complex Dynamics of the family - Salma Faris (Al-Rafidain Journal of Computer Sciences and Mathematics)
The aim of this work is to study the complex dynamics of the family   F={ ,}, of transcendental meromorphic functions. We prove that certain intervals are contained in J(f) or in F(f ) and we prove  that Julia set contains and show that Fatou set of the functions in F contains certain components for different values of . We characterize Julia set of  , for different values of, as the closure of the escaping points, and use this characterization to give computer images for these sets.